2018
DOI: 10.15406/hpmij.2018.02.00122
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication practice and associated factors among non-health professional students of university of Gondar, North West Ethiopia, 2017

Abstract: Introduction: The misuse of drugs among students has become a serious problem. In economically deprived countries most episodes of illness are treated by self medication. Major problems related to self medication are: wastage of resources, increased resistance of Pathogens, and generally entails serious health hazards such as adverse reaction and prolonged suffering. Objective: To assess the prevalence and associated factors of self medication practice among non health professional students of university of Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Accordingly, a study done by Helal & Abou-ElWafa (2017) has reported that believing consultation for mild illnesses is unnecessary (73.9%) and knowledge with prior use of SM (71.4%) were the most common reasons that led the participants to use SMP. Another study done in Ethiopia (Mekonnen, Zelalem & Tezera, 2018) also has presented with similar results by having most participants who have engaged in SMP due to the mildness of the illness (34.1%), and due to having prior good experience of SM (24.8%). The overall SMP of the study sample were further categorized into two levels as, 'high levels of SMP' and 'low levels of SMP' based on having four or more of the above SMP and having less than four of the above SMP, respectively.…”
Section: Reasons For Smpsupporting
confidence: 52%
“…Accordingly, a study done by Helal & Abou-ElWafa (2017) has reported that believing consultation for mild illnesses is unnecessary (73.9%) and knowledge with prior use of SM (71.4%) were the most common reasons that led the participants to use SMP. Another study done in Ethiopia (Mekonnen, Zelalem & Tezera, 2018) also has presented with similar results by having most participants who have engaged in SMP due to the mildness of the illness (34.1%), and due to having prior good experience of SM (24.8%). The overall SMP of the study sample were further categorized into two levels as, 'high levels of SMP' and 'low levels of SMP' based on having four or more of the above SMP and having less than four of the above SMP, respectively.…”
Section: Reasons For Smpsupporting
confidence: 52%
“…have shown that around 40% of the participants followed the prescription given by physicians during their previous disease exposure during self-medication. [ 4 5 ] A study by Niwandinda et al . also showed that 55.8% of the participants relied on pharmacists for information on self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…Patient Preference and Adherence 2022:16 3168 mildness of the illness, similarity of disease conditions with previous symptoms and incapability to afford health care costs were also reported as the major reasons for SM practice in other similar studies. 75,76 Conversely, saving time and money are the least common reasons for health science students in Eritrea where previous experience and perceived sufficient knowledge towards SM were the prior reasons. 39 However, self-treating perceived illnesses based on past experiences or with perceived knowledge without accurate diagnosis could lead to misdiagnosis, missed therapeutics, and subsequent unwanted health problems.…”
Section: Dovepressmentioning
confidence: 99%